The effect of positive end-expiratory pressure during anesthesia on arterial oxygen saturation after surgery in patient undergoing cesarean section - Mahmood Ganjifard; Masoumeh Samii; Samaneh Kouzegaran; Amir Sabertanha (PAGEPress Publications, 2018)
One of the major complications of general anesthesia in the recovery room is arterial oxygen desaturation and hypoxemia. Positive end-expiratory pressure (PEEP) can improve arterial oxygen saturation by increasing FRC. This study aims to evaluate the effects of applying PEEP on arterial oxygen saturation and hemodynamic parameters in the patient undergoing cesarean section in VALIASR hospital. In this double blind clinical trial we randomly allocated 120 patients of class1 and 2 ASA scheduled to undergoing cesarean section into 3 group (in 40).Different levels of PEEP (0, 5 and 10 CmH2o) were applied to each group while zero PEEP was established as control. All other variables (anesthesia and surgery techniques) were the same for all patients SPO2, noninvasive mean arterial pressure and heart rate were measured before, during and after surgery (Recovery room). The comparison of noninvasive arterial blood pressure and heart rate during and after surgery did not show significant differences but mean o2 saturation in group B (5 cmH2o PEEP) and C (10 cm H2o PEEP) in PACU was higher than control group (98.30±0.93 and 98.50±0.90 as opposed to97.12±1.15 respectively) P0<001. In light of results applying PEEP is effective in preventing desaturation after surgery and improving respiratory indexes without the significant hemodynamic changes, the result of using five cmH2o PEEP is more efficient and satisfying.